Alfred Schutz's Perspective in Phenomenology Approach: Concepts, Characteristics, Methods and Examples - Rasid, Ruslan; Djafar, Hilman; Santoso, Budi (International Journal of Educational Research & Social Sciences, 2021)
Alfred Schutz with his phenomenology introduced the concept of multiple reality. For Schutz, the reality in this world is not only in the reality of social life, but also includes fantasy reality, dream reality, etc. Therefore, the aim of this research is to analyze and describe how the concepts, characteristics, methods and examples of the use of the phenomenological approach in Alfred Schutz's perspective qualitative research methodology. The results of the study explain that the phenomenological approach pioneered by Edmund Husserl has a watchword: zuruck zu den sachen selbst (back to things themselves) that a method for explain phenomena in their purity, where these phenomena are anything that in some way appears in human consciousness . Whether in the form of something as a result of fiction or in the form of something real.